Exponential stability and numerical results of a thermoelastic Timoshenko system with diffusion effect, memory and distributed delay terms - Laribi I.; Krelifa A.; Boukabcha H.; Ouchenane D.; Boulaaras S.; Zitouni S.; Jan R. (Springer Science and Business Media Deutschland GmbH, 2025)
In this paper, we study the thermoelastic Timoshenko system with diffusion effect, memory, and distributed delay terms when they act on the second equation. Firstly, we use the Faedo?Galerkin method to show the well-posedness of the system. Then, we study the exponential stability using the Lyapunov functional. Next, we introduce a finite element scheme of the problem, and then we establish the discrete energy decay. Finally, we give a priori error estimates and some numerical simulations. ? The Author(s) 2024.